2020
DOI: 10.2196/20579
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Creating Scalable Business Models for Digital Health Innovation in Public Systems: Qualitative Case Study

Abstract: Background Health systems are increasingly looking toward the private sector to provide digital solutions to address health care demands. Innovation in digital health is largely driven by small- and medium-sized enterprises (SMEs), yet these companies experience significant barriers to entry, especially in public health systems. Complex and fragmented care models, alongside a myriad of relevant stakeholders (eg, purchasers, providers, and producers of health care products), make developing value pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…A handful of other studies have shown similar results. 30 32 For instance, Kelley et al 30 reported that one of the barriers to implementing sustainable digital health business models in health systems is that the benefits/savings accrue at the system level (e.g. avoiding transfers and travel, improved patient health outcomes), without being reflected in organisational performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A handful of other studies have shown similar results. 30 32 For instance, Kelley et al 30 reported that one of the barriers to implementing sustainable digital health business models in health systems is that the benefits/savings accrue at the system level (e.g. avoiding transfers and travel, improved patient health outcomes), without being reflected in organisational performance outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Flexibility in interventions that allow for some degree of personalization, such as activating or deactivating features based on personal preferences and the ability to alter intervention design based on comorbidities (eg, visual impairments and hand osteoarthritis), may also foster adherence [ 106 ]. From the clinician’s perspective, reimbursement models that incentivize the use of digital health interventions are needed [ 115 ]. Although these findings provide some guidance, the best practice would be to include all stakeholders (clinicians and patients) while developing new digital health interventions [ 116 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 21 For example, incentives could be created to support the use of an innovation, such as a payment system that covers its costs. 48 Incentives are also facilitators for scaling de-implementation strategies. This framework adds the recommendation to also remove incentives for the use of LVC to support the scaling of de-implementation strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the literature on the scaling of innovations, for example, Rogers’ diffusion of innovations theory and the Consolidated Framework for Implementation Research, we have added several topics and nuanced the implications of the shared subdomains and determinants 18 21. For example, incentives could be created to support the use of an innovation, such as a payment system that covers its costs 48. Incentives are also facilitators for scaling de-implementation strategies.…”
Section: Discussionmentioning
confidence: 99%